Residual Information of Previous Decision Affects Evidence Accumulation in Current Decision - Olianezhad, Farzaneh; Zabbah, Sajjad; Tohidi-Moghaddam, Maryam; Ebrahimpour, Reza (Frontiers in Behavioral Neuroscience, 2019)
Bias in perceptual decisions can be generally defined as an effect which is controlled by factors other than the decision-relevant information (e.g. perceptual information in a perceptual task, when trials are independent). The literature on decision-making suggests two main hypotheses to account for this kind of bias: internal bias signals are derived from (a) the residual of motor signals generated to report a decision in the past, and (b) the residual of sensory information extracted from the stimulus in the past. Beside these hypotheses, this study suggests that making a decision in the past per se may bias the next decision. We demonstrate the validity of this assumption, first, by performing behavioral experiments based on the two-alternative forced-choice (TAFC) discrimination of motion direction paradigms and, then, we modified the pure drift-diffusion model (DDM) based on the accumulation-to-bound mechanism to account for the sequential effect. In both cases, the trace of the previous trial influences the current decision. Results indicate that the probability of being correct in the current decision increases if it is in line with the previously made decision even in the presence of feedback. Moreover, a modified model that keeps the previous decision information in the starting point of evidence accumulation provides a better fit to the behavioral data. Our findings suggest that the activity of decision-related neuron after crossing the bound in the previous decision can affect the parameters of information accumulation for the current decision in consecutive trials.